2004
DOI: 10.1002/jsfa.1748
|View full text |Cite
|
Sign up to set email alerts
|

Impact of γ‐irradiation and thermal processing on the antigenicity of almond, cashew nut and walnut proteins

Abstract: Whole unprocessed almonds, cashew nuts and walnuts were each subjected to γ -irradiation (1, 5, 10 and 25 kGy) followed by heat processing including autoclaving (121 • C, 15 psi for 15 and 30 min), dry roasting (138 and 160 • C for 30 min each, 168 and 177 • C for 12 min each), blanching (100 • C for 5 and 10 min), oil roasting (191 • C, 1 min) and microwave heating (500 W for 1 and 3 min). Rabbit polyclonal antibodies were raised against each major protein isolated from defatted, but not subjected to γ -irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 26 publications
11
74
0
Order By: Relevance
“…However, despite the absence of intact protein, hydrolysates maintained IgE-and IgGbinding capacity on account of the formation of long hydrophobic peptides, which retained sequential epitopes. In contrast, the IgE-binding capacity of almond, cashew nut and walnut proteins remained stable after γ-irradiation (1-25 kGy) even when combined with common thermal processing methods, including autoclaving, dry roasting, blanching, oil roasting and microwave heating (Su et al, 2004).…”
Section: Multiple Treatmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, despite the absence of intact protein, hydrolysates maintained IgE-and IgGbinding capacity on account of the formation of long hydrophobic peptides, which retained sequential epitopes. In contrast, the IgE-binding capacity of almond, cashew nut and walnut proteins remained stable after γ-irradiation (1-25 kGy) even when combined with common thermal processing methods, including autoclaving, dry roasting, blanching, oil roasting and microwave heating (Su et al, 2004).…”
Section: Multiple Treatmentsmentioning
confidence: 95%
“…Antigenic stability of proteins in several nuts subjected to various processing methods, including γ-irradiation alone or in combination with blanching, pressure cooking, oven roasting, frying and microwave heating, was demonstrated using Western blotting and ELISA (Su et al, 2004). While heat processing may inactivate certain structural epitopes of hazelnuts, such treatments are unlikely to affect the allergenicity of almonds, cashew nuts and walnuts.…”
Section: Other Treatmentsmentioning
confidence: 99%
“…Similarly, in studies with cashew nuts, Su et al and Venkatachalam et al [40,41] used doses up to 25 kGy where the major allergens showed stability. In contrast, Byun et al [42] found effects of decreasing allergenicity of potentially allergenic foods as increasing dose of gamma radiation used, aiming beta-lactoglobulin protein in cow's milk, hen egg albumin, and shrimp tropomyosin using doses up to 10 kGy as shown in (Figure 2).…”
Section: New Insights On Gamma Raysmentioning
confidence: 99%
“…A study by Su et al (2004) evaluated the antigenicity of whole unprocessed almonds, cashew nuts and walnuts after gammairradiation (using doses between 1 and 25 kGy) followed by heat treatments such as autoclaving (121°C, 15 psi for 15 and 30min), dry-roasting (138 and 160°C for 30 min each, 168 and 177°C for 12 min each), blanching (100°C for 5 and 10 min), oil roasting (191°C, 1min) and microwave heating (500W for 1 and 3min). Immunoreactivity was determined through ELISA and Western blotting experiments using rabbit polyclonal antibodies raised against each major protein.…”
Section: Allergenicitymentioning
confidence: 99%